Proceedings of the 2016 4th International Conference on Electrical &Amp; Electronics Engineering and Computer Science (ICEEECS 2016
DOI: 10.2991/iceeecs-16.2016.186
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Bee Colony Algorithm for Image Restoration

Abstract: This paper proposes a new method for image restoration using artificial bee colony algorithm (ABC algorithm). ABC algorithm combined with wiener filter is used to restore image. In the fuzzy identification, ABC algorithm is used for optimization the point spread function (PSF). In the restoring part, wiener filter is used for image restoration. Proposed method overcomes the problem of the traditional image restoring, which needs to know the PSF in advance. In addition, this method improves the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Khader AT et al in their survey of literature suggested that ABC algorithm have been applied to many different areas such as engineering design applications, bioinformatics applications, image processing applications and benchmarking optimizations [5]. Jie Yang et al, in 2016 proposed a new method for image restoration using ABC algorithm by combining it with wiener filter and showed that this method is better for image restoration [6]. In 2017, Linguo Li et al applied ABC algorithm for multi level thresholding of images and the experimental results showed that this method can search out the optimal thresholds efficiently, precisely, and speedily, and the thresholds are very close to the results examined by exhaustive searches [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Khader AT et al in their survey of literature suggested that ABC algorithm have been applied to many different areas such as engineering design applications, bioinformatics applications, image processing applications and benchmarking optimizations [5]. Jie Yang et al, in 2016 proposed a new method for image restoration using ABC algorithm by combining it with wiener filter and showed that this method is better for image restoration [6]. In 2017, Linguo Li et al applied ABC algorithm for multi level thresholding of images and the experimental results showed that this method can search out the optimal thresholds efficiently, precisely, and speedily, and the thresholds are very close to the results examined by exhaustive searches [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yigitbasi ED et al in their work in 2013, done out the control detection by ABC and the outcomes exhibited better than the approaches of Sobel and Roberts for border detection with median filter [10]. [11,12]. In 2017, Li et al used ABC algorithm for multi-level thresholding of images and the experimental outcomes presented that this technique can search out the ideal thresholds efficiently and speedily, and the thresholds are very nearby to the outcomes studied by comprehensive examinations [13].…”
Section: Introductionmentioning
confidence: 99%